Design of System for Monitoring Seepage of Levee Engineering Based on Distributed Optical Fiber Sensing Technology - Huaizhi Su; Yeyuan Kang (International Journal of Distributed Sensor Networks)
Seepage is the major factor and monitoring index of levee safety. Leakage may be undetected by conventional monitoring methods and techniques, but optical fiber distributed temperature sensor (DTS) temperature measuring system can achieve real-time temperature monitoring in internal soil of levees. According to the temperature field obtained by DTS system, monitoring and inversion methods of seepage velocity based on double-line heat source and single-line heat source are introduced, respectively. An experiment is designed and composed of DTS temperature measuring system, the heating system, the water supply system, and the computer-aided analysis system to test and verify the effectiveness and feasibility of the monitoring method. On this basis, the system of monitoring seepage based on distributed optical fibers is put forward and designed. Optical fiber intelligent monitoring system will improve the current situation of safety monitoring of levee engineering on the basis of its unique superiority.